Kenya and distance education: a model to advance graduate nursing - Mutea, Naomi K.; Cullen, D.L. (Blackwell Publishing Ltd, 2012)
Africa is faced with a myriad of challenges, such as HIV/AIDS, malaria, tuberculosis, and a variety of political and historical complications that have affected the educational system for advanced nursing practice. In Kenya, the current situation in the higher education sector does not give nurses an opportunity to pursue graduate education after they have acquired the basic diploma in nursing due to limited government support and the type of education system existing in the country today. Although distance education has been available in Kenya for professionals such as teachers, in public universities, this kind of opportunity is unreachable for nurses who are working and need to further their education. Nurses desire to have access to advanced practice education to equip them with the relevant knowledge to cope and address the complex health issues arising in the management and care of patients. A collaborative model is presented as a potential solution for this need. Four major constituents are identified including hospitals and agencies, communities of interest, Kenyan universities and international education partners. Each has a part to play including contributions to information, communication of opinion and expertise, money and support, infrastructure and in-kind resources. Distance education is cost-effective and will help in building capacity at various levels of nursing including leadership in clinical practice, teaching, administration and research.
doi: 10.1111/j.1440-172X.2012.02043.x